Designing an Android-Based E-Commerce Application for Picci-Picci Traditional Handicraft Products at the Craftsman Group of BUMDes Mamuju Tengah - Ega Lestari; Johan J.C. Tambotoh (Budapest International Research and Critics University, 2022)
The sale of traditional goods picci - picci BUMDes Mamuju Tengah based on android application is made to make it easier for the public to find out information about the latest traditional products available in BUMDes. This study uses research methods such as observation, interviews and literature study. As for the system development method using Design Science Research (DSR). Based on the results of research with the design of this information system, it can facilitate the dissemination of information about the latest products available in the BUMDes of Mamuju Tengah and facilitate the processing of sales transaction data and information.